Biohydrogen production in semi-continuous system using immobilized cell membrane - Engliman, Nurul Sakinah; Abdul Aziz, Ainul Husna; Abdul, Peer Mohamed; Luthfi, Abdullah Amru Indera; Jahim, Jamaliah M.D.; Jamali, Nur Syakina (International Islamic University Malaysia-IIUM, 2024)
Hydrogen is considered to be the fuel of the future because of its high energy content (122 kJ/g), and water is the only byproduct of its use. Moreover, the production of hydrogen via fermentation of organic wastes is carbon neutral. This study was conducted to evaluate the performance of immobilized cells on PVDF membrane for biohydrogen production using a sequencing batch reactor by varying the hydraulic retention times (HRT) of the system and to compare the efficiency between suspended and attached systems on the production of biohydrogen. It was found that the biohydrogen fermentation performance was improved in a semi-continuous system, especially with immobilized cells. The optimum HRT that supports the highest biohydrogen yield was for an HRT of 12 hours, where the performance of hydrogen production was improved and in which the maximum hydrogen yield was achieved at 2.43 mol H2/mol and maximum hydrogen production rate (HPR) of 2.46 L H2/L.d as compared to other HRT for both systems. Therefore, the result of this study can be applied as the benchmark for scaling up the process.